2017
DOI: 10.1177/0021998317695423
|View full text |Cite
|
Sign up to set email alerts
|

Experimental tests and numerical modeling of ballistic impact on honeycomb sandwich structures reinforced by functionally graded plates

Abstract: The aim of this study is to determine the ballistic impact response of a novel sandwich structure consisting of aluminum honeycomb and Al/SiC functionally graded face sheets and develop a compatible numerical model with experiments. The experiments were carried out by a single-stage gas gun system and numerical simulations were performed using the explicit finite element code, LS-DYNA®. The mechanical properties of the functionally graded face sheets through the thickness were considered in accordance with a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 32 publications
0
12
0
1
Order By: Relevance
“…According to the TTO model, 23,32,55 the composite material yields when the metal constituent yields. Thus, the yield stress σLy of the composite material (i.e.,.…”
Section: Methodsmentioning
confidence: 99%
“…According to the TTO model, 23,32,55 the composite material yields when the metal constituent yields. Thus, the yield stress σLy of the composite material (i.e.,.…”
Section: Methodsmentioning
confidence: 99%
“…They concluded that when the faceplate is ceramic-rich (n=10.0), the ballistic velocity limit can reach the maximum value. A similar experimentation suggests that the projectile retains 37% kinetic energy when the faceplate is metal-rich, in contrast to the ceramic-rich faceplates when 97.4% kinetic energy is absorbed successfully [17]. More recently, Zhao et al [18] investigated the potentiality of an injection-molded composite sandwich bulletproof system and concluded that the ballistic resistance can be improved greatly in contrast to the non-injection molded system.…”
Section: State Of the Artmentioning
confidence: 98%
“…Honeycomb sandwich panels play a pivotal role in aerospace structures, automotive, marine, and biomedical applications due to the high strength-to-density, high energy absorption capability, high stiffness-to-density properties, and high fatigue resistance. 14 Among the honeycomb structures, the auxetic honeycomb with re-entrant cell shape and negative Poisson’s ratio have specific properties such as higher shear resistance, higher energy absorption, and crashworthiness with the lower natural frequency with respect to other cell shape types. 5–7 The dynamic performance of sandwich panels with re-entrant cell shape core are studied by considering the influence of negative Poisson’s ratio on natural frequencies and bending behavior.…”
Section: Introductionmentioning
confidence: 99%